2017
DOI: 10.7196/samj.2017.v108i1.12825
|View full text |Cite
|
Sign up to set email alerts
|

South African clinical practice guidelines: A landscape analysis

Abstract: Background. South Africa (SA) is in the process of implementing National Health Insurance (NHI), which will require co-ordination of health provision across sectors and levels of care. Clinical practice guidelines (CPGs) are tools for standardising and implementing care, and are intended to influence clinical decision-making with consequences for patient outcomes, health system costs and resource use. Under NHI, CPGs will be used to guide the provision of healthcare for South Africans. It is therefore importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Participants specifically suggested that outcome measures must be multi-disciplinary and holistic. This suggestion is in line with the person-centred approach current advocated by the South African Department of Health [ 22 – 24 ].…”
Section: Resultssupporting
confidence: 75%
“…Participants specifically suggested that outcome measures must be multi-disciplinary and holistic. This suggestion is in line with the person-centred approach current advocated by the South African Department of Health [ 22 – 24 ].…”
Section: Resultssupporting
confidence: 75%
“…Guideline quality in prehospital care was also raised as a concern, a sentiment prevalent across various disciplines, from primary health care to allied health [ 4 , 6 , 11 ]. Furthermore, a similar landscape analysis conducted of only South African guidance documents highlighted the lack of emergency care guidance available [ 12 ]. Guidance document quality seems to be a concern for LMICs, possibly due to their lack of formal guidance document organisations, technical capacity, or collaborations to develop evidence-based guidance documents [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…South Africa has long been developing CPGs, most pronounced during the post-apartheid period when CPGs were considered important tools to redress inequity, standardise care and promote cost-effective care for all. Many CPG development players have been identified: national government, professional societies, hospitals and clinics all contribute according to their needs and agendas [6, 7]. However, despite development and distribution of CPGs, health outcomes remain poor, and generally worse than expected given the per capita health spend relative to other similar middle-income countries [8, 9].…”
Section: Introductionmentioning
confidence: 99%